2011
DOI: 10.3892/ijmm.2011.619
|View full text |Cite
|
Sign up to set email alerts
|

Roles of exogenously regulated bFGF expression in angiogenesis and bone regeneration in rat calvarial defects

Abstract: Abstract. Regulation of transgene expression and function is important for gene therapy because it allows complex biological processes to be controlled and monitored. Basic fibroblast growth factor (bFGF) is an effective angiogenic factor and bone regeneration factor; it can induce differentiation of mesenchymal stem cells (MSCs) in vitro and bone regeneration in vivo. Further, exogenous regulation of controllable bFGF expression in the bone regeneration area safely allows bone formation and regeneration. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The anabolic effect of bFGF in vivo could result from the brief exposure of local cells to the released proteins, prompting osteogenic differentiation. In addition, bFGF regulates angiogenesis, cell migration, and cell proliferation [ 71 , 72 ]. Hence, these processes could help to facilitate the healing and formation of hard tissue in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The anabolic effect of bFGF in vivo could result from the brief exposure of local cells to the released proteins, prompting osteogenic differentiation. In addition, bFGF regulates angiogenesis, cell migration, and cell proliferation [ 71 , 72 ]. Hence, these processes could help to facilitate the healing and formation of hard tissue in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has mostly focused on the secretion of angiogenic factors by undifferentiated bone marrow derived MSCs such as mesenchymal progenitor cells, marrow-derived stromal cells and multipotent stromal cells [ 79 81 ]; moreover, recent studies reported that the osteogenically differentiated MSCs that cultured in osteogenic induction medium could lead cells antiangiogenic and reduce the secretion of angiogenic factors like VEGF and platelet-derived growth factor-AA (PDGF-AA) [ 82 , 83 ]. However, many studies reported that some growth factors such as BMP-2 [ 84 , 85 ], BMP-9 [ 86 ], epidermal growth factor (EGF) [ 87 ], growth and differentiation factor-5 (GDF-5) [ 88 ] and basic fibroblast growth factor (bFGF) [ 84 , 89 , 90 ], could promote osteogenic differentiation of MSCs as well as secretion of angiogenic factors by inducing both osteogenic and angiogenic signaling pathways without osteogenic induction medium. In the present study, it has been firstly observed that as a kind of Chinese medicine, quercetin could not only promote osteogenic differentiation of rBMSCs, but also enhance the secretion of angiogenic factors in a dose-dependent manner, while the concentration of 2 μM could achieve the greatest effect.…”
Section: Discussionmentioning
confidence: 99%
“…Among the known BMPs, BMP-2 has the most pronounced effect on promoting defect repair and in healing fractures [33]. bFGF, a potent angiogenic factor and bone regeneration factor, induces specialization of MSCs in vitro and bone repair in vivo [17]. bFGF-modified BMSCs could accelerate healing after anterior cruciate ligament (ACL) reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-2, one of the most effective osteoinductive proteins, facilitates osteoblast differentiation, and prior studies have demonstrated that bone repair can be accomplished through the application of BMP-2 [14, 16]. Basic fibroblast growth factor (bFGF) has important roles in a wide variety of cellular functions, including cell multiplication and angiogenesis [17], and due to its effects on gene expression and angiogenesis, it is a key factor during bone repair [18]. Adenovirus vectors have proven to be potent gene delivery vehicles that can be used to genetically manipulate cells [19].…”
Section: Introductionmentioning
confidence: 99%